GLP-1R as a potential link between diabetes and Alzheimer’s disease - Li, Shujun; Huang, Nanqu; Wang, Mei; Huang, Wendi; Shi, Jingshan; Luo, Yong; Huang, Juan (Frontiers in Aging Neuroscience, 2025)
There is growing interest in the relationship between Alzheimer’s disease (AD) and diabetes mellitus (DM), and the glucagon-like peptide-1 receptor (GLP-1R) may be an important link between these two diseases. The role of GLP-1R in DM is principally to regulate glycemic control by stimulating insulin secretion, inhibiting glucagon secretion, and improving insulin signaling, thereby reducing blood glucose levels. In AD, GLP-1R attenuates the pathological features of AD through mechanisms such as anti-inflammatory effects, the reduction in amyloid-beta (Aβ) deposition, the promotion of Aβ clearance, and improvements in insulin signaling. Notably, AD and DM share numerous pathophysiological mechanisms, most notably the disruption of insulin signaling pathways in the brain. These findings further underscore the notion that GLP-1R plays pivotal roles in both diseases. Taken together, these findings lead us to conclude that GLP-1R not only plays an important role in the treatment of DM and AD but also may serve as a bridge between these two diseases. Future research should focus on elucidating the detailed molecular mechanisms underlying the actions of GLP-1R in both diseases and exploring the development of GLP-1R agonists with dual therapeutic benefits for AD and DM. This could pave the way for innovative integrated treatment strategies to improve outcomes for patients affected by these intertwined conditions.